2020
DOI: 10.1016/j.celrep.2020.108524
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Cerebrospinal Fluid Production in Mice

Abstract: SUMMARY The emerging interest in brain fluid transport has prompted a need for techniques that provide an understanding of what factors regulate cerebrospinal fluid (CSF) production. Here, we describe a methodology for direct quantification of CSF production in awake mice. We measure CSF production by placing a catheter in a lateral ventricle, while physically blocking outflow from the 4 th ventricle. Using this methodology, we show that CSF production increases during isoflur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
74
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 65 publications
(89 reference statements)
5
74
3
Order By: Relevance
“…Glymphatic function drops dramatically during aging due to various factors. Reduced polarized aquaporin-4 channels on the endfeet of astrocyte cells ( Valenza et al, 2019 ), decreased CSF production ( Liu et al, 2020 ) and CSF pressure, diminished arterial pulsatility ( Mestre et al, 2018b ) could all lead to compromised glymphatic function in aged animals ( Jessen et al, 2015 ). In a recent study, Zhou Y. et al (2020) .…”
Section: Discussionmentioning
confidence: 99%
“…Glymphatic function drops dramatically during aging due to various factors. Reduced polarized aquaporin-4 channels on the endfeet of astrocyte cells ( Valenza et al, 2019 ), decreased CSF production ( Liu et al, 2020 ) and CSF pressure, diminished arterial pulsatility ( Mestre et al, 2018b ) could all lead to compromised glymphatic function in aged animals ( Jessen et al, 2015 ). In a recent study, Zhou Y. et al (2020) .…”
Section: Discussionmentioning
confidence: 99%
“…Current study quantified the flow rate of ICF, i.e., 891-1153 ml/100ml/min in LV and 3V. A recent invasive study on mouse brain states the CSF outflow from both LV and 3V is in the order of magnitude of 0.1 µL/min (48), which is minute compare to the ICF flow obtained by our current study (32-44 µL/min in 4 µL LV). Our result indicated that the CSF secreted from parenchyma is reabsorbed by the periventricular ependymal layers as indicated in Fig.…”
Section: Discussionmentioning
confidence: 46%
“…Water continuously moves in and out of the ependymal layer, a process resembles the intracellular and extracellular water movement, is one possible reason for the rapid turnover number. The difference between CSF secreted from CP (0.52-0.8 µL/min) (47) and the total outflow (0.1 µL/min) (48) suggests that a large portion of the CSF in ventricles is absorbed by the surrounding parenchyma. But due to the large mass of the parenchyma, kinetically speaking, the absorption is a prolonged process (less than 15 ml/100mg/min) as confirmed by the T2-PALAN measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Increased sympathetic tone inhibits carbonic anhydrase associated with the choroidal epithelium and likely reduces CSF production and glymphatic circulation (Damkier et al, 2013 ; Benveniste et al, 2017 ). Recently, Liu et al also reported that CSF production was increased by a combination of α 1 -, α 2 -, and non-selective β-adrenergic receptor antagonists, as well as some anesthetics, including isoflurane, ketamine, and xylazine (Liu G. et al, 2020 ).…”
Section: The Underlying Mechanism Of Altered Glymphatic Function During Intraoperative Anesthesia Managementmentioning
confidence: 99%